Provisional best practices guidelines for the evaluation of bulbar dysfunction in amyotrophic lateral sclerosis. Issue 5 (22nd January 2019) - Pattee, Gary L.; Plowman, Emily K.; (Focht) Garand, Kendrea L.; Costello, John; Brooks, Benjamin Rix; Berry, James D.; Smith, Richard A.; Atassi, Nazem; Chapin, Jennifer L.; Yunusova, Yana; McIlduff, Courtney E.; Young, Eufrosina; et al.
Abstract: Introduction : Universally established comprehensive clinical bulbar scales objectively assessing disease progression in amyotrophic lateral sclerosis (ALS) are currently lacking. The goal of this working group project is to design a best practice set of provisional bulbar ALS guidelines, available for immediate implementation within all ALS clinics. Methods : ALS specialists across multiple related disciplines participated in a series of clinical bulbar symposia, intending to identify and summarize the currently accepted best practices for the assessment and management of bulbar dysfunction in ALS Results : Summary group recommendations for individual speech, Augmentative and Alternative Communication (AAC), and swallowing sections were achieved, focusing on the optimal proposed level of care within each domain. Discussion : We have identified specific clinical recommendations for each of the 3 domains of bulbar functioning, available for incorporation within all ALS clinics. Future directions will be to establish a formal set of bulbar guidelines through a methodological and evidence‐based approach. Muscle Nerve 59:531–531, 2019 Abstract : See editorial on pages 523–524 in this issue .